Mediterranean Diet reduces ischemic heart disease risk in diabetes patients until reversed by smoking: Evidence from UK Biobank cohort - Yongna Fan; Lihua Li; Fengjun Du; Jie Ren; Jing Dong; Bingyin Zhang; Xiaolei Guo; Yueqing Huang; Danru Liu; Jixiang Ma (PLoS ONE, 2025)
Objectives This study aims to explore the association between the Mediterranean Diet (MD) pattern and the development of ischemic heart disease (IHD) in patients with diabetes mellitus (DM) to provide a scientific basis for the management of diabetic patients. Methods Based on 7606 participants from the UK Biobank cohort, the adherence to the MD was assessed. The outcome indicator was the occurrence of IHD. Cox proportional hazards model was applied to estimate the Hazard ratios (HR) and 95% confidence interval (CI) of the Mediterranean Diet Score (MDS) and IHD, while trend analysis was performed using the Wald trend test. Subgroup and interaction analyses considered factors. Results Among 7,606 diabetic patients with a mean follow-up of 13.04 years, a total of 1,173 new cases of IHD were reported. After multivariable adjustment, a higher MDS was negatively associated with the incidence of IHD in diabetic patients. Additionally, compared with the Q1 group, the Q4 group had a 18.5% lower risk of IHD occurrence. Trend tests were statistically significant ( P -values < 0.001 for all four models). Subgroup analyses showed benefits in white people, males, high-income earners, non smokers and previous smokers, but a positive association in current smokers. Only gender, income, and smoking showing multiplicative interactions with MDS. Sensitivity analysis demonstrated effect modification by physical activity and education level, which was not observed in the primary analysis. Conclusions The MD pattern can effectively reduce the incidence of IHD in diabetic patients, and gender, income and smoking have modifying effects on the MD pattern.